2019
DOI: 10.3389/fpsyg.2018.02740
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Fighting Ability Inferences Based on Faces

Abstract: Facial perception plays a key role in various social interactions, including formidability assessments. People make relatively accurate inferences about men's physical strength, aggressiveness, and success in physical confrontations based on facial cues. The physical factors related to the perception of fighting ability and their relative contribution have not been investigated yet, since most existing studies employed only a limited number of threat potential measures or proxies. In the present study, we coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…People can accurately assess physical strength from body 19 and face 66 images. For example, sexually dimorphic facial cues predict fighting ability among MMA fighters 33 , 67 but see 68 , and using these cues participants can predict fighting outcomes above chance 69 . The voice appears to be another aspect of the phenotype that indicates formidability 10 , 13 , 19 ; we showed that f o was associated with both body size and fighting experience (independent of body size) among male MMA fighters.…”
Section: Discussionmentioning
confidence: 99%
“…People can accurately assess physical strength from body 19 and face 66 images. For example, sexually dimorphic facial cues predict fighting ability among MMA fighters 33 , 67 but see 68 , and using these cues participants can predict fighting outcomes above chance 69 . The voice appears to be another aspect of the phenotype that indicates formidability 10 , 13 , 19 ; we showed that f o was associated with both body size and fighting experience (independent of body size) among male MMA fighters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated, for instance, that people can relatively accurately assess physical strength from images of body and face (Sell et al, 2009a; Holzleitner and Perrett, 2016; Kordsmeyer et al, 2018). Moreover, it seems that based on facial images raters can predict winners of mixed martial arts (MMA) fights (Třebický et al, 2013; Little et al, 2015; but see Třebický et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 Given that: (1) there have only been a limited number of draws in the UFC (i.e., approximately 40 out of over 5000 UFC fights; out of our sample of 520 fighters, only one fighter had been in three draws, eight fighters had been in two draws, and 54 fighters had been in one draw); (2) that the vast majority of UFC research has not accounted for draws in their research (e.g., Aung et al, 2021;Třebický et al, 2013Třebický et al, , 2019Zilioli et al, 2014); and that (3) draws might not be appropriate for capturing RHP (as an indicator of an organism's ability to win a fight), we decided not to account for draws in this data but rather to adopt the most commonly used measure of fight success (i.e., total wins divided by total fights).…”
Section: Discussionmentioning
confidence: 99%
“…To directly replicate the original study, which controlled for body mass index (BMI) rather than weight or height themselves, we calculated BMI ( M = 23.70; SD = 3.42) using the formula: weight (lbs)/(height[inches] × height[inches]) × 703 (with 703 being the number used to convert lbs/inches 2 to kg/m 2 ). In accord with the original study, we calculated fight success ( M = 0.79; SD = 0.11) using previously published methods (Třebický et al, 2013, 2019; Zilioli et al, 2014) whereby the total number of wins were divided by the total number of fights 2…”
Section: Study 1: Automatic Fwhr Measurementsmentioning
confidence: 99%